2010
DOI: 10.1103/physrevc.82.044607
|View full text |Cite
|
Sign up to set email alerts
|

Probing the potential and reaction coupling effects ofLi6,7+Si28

Abstract: The excitation functions for 7 Li + 28 Si quasielastic scattering at 150 • and 170 • have been measured at suband near-barrier energies (0.6 to 1.3 V B ) and the corresponding barrier distributions derived. The results were analyzed within the framework of the optical model using a procedure similar to one used on previous results for 6 Li + 28 Si employing double-folded potentials calculated using the BDM3Y1 effective interaction. The variation of the surface strength of the optical potential as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
5
15
0
Order By: Relevance
“…This has been observed for 58 Ni + 58 Ni, 90 Zr + 92 Zr and 60 Ni + 89 Y, and more recently similar results have been obtained for several other systems [312][313][314][315][316]. Before we discuss the physics involved in this phenomenon, one should understand clearly what one means by hindrance.…”
Section: Hindrance Of Fusion At Deep Sub-barrier Energiessupporting
confidence: 64%
“…This has been observed for 58 Ni + 58 Ni, 90 Zr + 92 Zr and 60 Ni + 89 Y, and more recently similar results have been obtained for several other systems [312][313][314][315][316]. Before we discuss the physics involved in this phenomenon, one should understand clearly what one means by hindrance.…”
Section: Hindrance Of Fusion At Deep Sub-barrier Energiessupporting
confidence: 64%
“…Owing to conservation of the reaction flux, the fusion and QEL scattering process can be considered complementary and barrier distributions obtained from both types of measurements are expected to be similar [8]. Recently such studies have been carried out using weakly bound stable nuclei [9][10][11][12][13][14][15]. In some cases [9,10,13] it has been found that the barrier distribution obtained from QEL scattering including only the elastic + inelastic + transfer channels peaks at a lower energy compared to the corresponding barrier distribution obtained from fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of fusion barrier distributions for systems with weakly bound projectiles have been reported about a decade ago [16][17][18][19]. QEL and elastic-scattering barrier distributions for systems involving weakly bound nuclei have been studied only recently [12,[20][21][22][23][24][25][26], with the exception of Ref. [17].…”
Section: Introductionmentioning
confidence: 99%